Typo-technological, elemental and lead isotopic characterization and interpretation of Đông Sơn miniature drums. (August 2021) - Le Meur, Clémence; Cadet, Mélissa; Doan, Nguyen Van; Trien, Dinh Ngoc; Cloquet, Christophe; Dillmann, Philippe; Thote, Alain; Pryce, T.O.
Highlights: Miniature Đông Sơn drum assemblages are found only in northern Việt Nam. 131 examined typo-technologically, 25 analyzed by OM, XRF, SEM-EDS and MC-ICP-MS. All 25 'as-cast' in 4 cross-typological alloy groups: Cu, Pb-Cu, Cu-Sn & Pb-Cu-Sn. LI ratios regionally-consistent and suggest two possible Pb groups but no source. Abstract: Copper-base drums are among the most iconic artefacts of mid-late 1st millennium BC Southeast Asia and southern China, and more specifically of the Vietnamese Đông Sơn culture and the Yunnanese Dian culture. The wide distribution of these drums, in public museums and private collections, renders their technical and stylistic study difficult, and their comparison complex. In this paper, we focus on a copper-base miniature drum assemblage, discovered in a tightly delimited area of northern Vietnam, associated to the Đông Sơn culture. This multi-disciplinary study incorporates morphological, stylistic, technological, elemental and lead isotopic analysis of a large proportion of a regional drum assemblage for the first time. With this combined approach was intended to improve our knowledge of the people who produced and consumed miniature drums; a class which, until now, has not aroused much interest. The present paper details the archaeometric results of this original analysis, based on 25 samples from the National Museum of History (Hanoi). The results indicate a wide variety of alloy types was used, alongside a range of raw material sources, both with weak correspondence to morpho-stylistic classification. We propose these data evidence Đông Sơn drum miniature production was practiced in a decentralised manner, using materials at hand, but questions concerning their emergence and their link to burial practices seen in contemporary southern China remains unsolved from an archaeometallurgical point of view but will be the subject of another paper (Le Meur et al . (forthcoming).